The design, synthesis, and antitubercular properties of the tri-substituted benzofuran derivatives - Mojapelo, Semola Kabelo (My University, 2025)
Tri-Substituted benzofuran derivatives exhibit greater biological activities influenced by natural compounds with highest potency, selectivity, and multifunctionality. Naturally occurring benzofuran with hydroxyl, methoxy, phenyl modification in different position showed antimicrobial, anticancer, antitubercular, and neuroprotective activities. These modification groups can influence lipophilicity, binding affinity and membrane permeability of mycobacterium tuberculosis which impact bioactivity. The aim of the study was to design, synthesise, and evaluate the anti-tubercular properties of the tri-substituted benzofuran derivatives. 5-iodovanillin 1B was made by iodinating commercially available vanillin 1A in a 92% yield. 2-(substituted)-7-methoxybenzofuran-5-carbaldehydes 2A-2E were produced by a Sonogashira cross-coupling reaction with palladium using a variety of acetylenes in a 60–80% yield. 2-(substituted)-7-methoxybenzofuran-5-carbaldehydes (2A-2E) were reduced with sodium borohydride in ethanol at room temperature, producing 2-substituted-7-methoxybenzofuran-5-ylmethanols (3A-3E) in a 60–82% yield. The esterification of the 2-substituted-7-methoxybenzofuran-5-carbaldehydes 3A-3E was catalysed by a Mukaiyama catalyst with several carboxylic acids in dichloromethane at room temperature, producing esters 3A1-3E5 in 40–80% yields. FTIR and NMR spectroscopy were used to characterise each of the synthesised substances. The online platform ADMET3.0 was used to perform the ADMET characteristics of esters 3A1-3E5. The antimycobacterial, cytotoxic, and solubility properties of every synthesised compound were assessed biologically. Several trisubstituted benzofuran derivatives that were synthesised demonstrated antimycobacterium tuberculosis (Mtb H37Rv) activity. For example, compound 3B3 showed good activity in all three media used with less toxicity. Additionally, six compounds (2A, 3A, 3A2, 2B, 3B, and 3B1) showed solubility results ranging between 5-195 μM. Compound 3B showed the best solubility of 195 μM but poor antitubercular activity in all three media used. On the contrary, compound 2A showed promising antimycobacterial activity of 2.02-18.08 μM in two media but had poor solubility of less than 5 μM. Additionally, compound 3A2 demonstrated activity in one medium (7H9/CAS/Glu/Tx), whereas compound 3B1 demonstrated activity in two media (7H9/ADC/Glu/Tw and 7H9/ADC/Glu/Tx). Both compounds displayed comparable outcomes, including good solubility at 50 μM and cytotoxicity at or above 50 μM, respectively.
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2025
Keywords: Antimycobacterial; Benzofuran; Antitubercular; Benzofuran; Synthesise; Design; Antitubercular agents; Benzofuran; Antimicrobial polymers